Albert Camus And Kierkegaard on Existential Isolation to Indonesia Citizen - Gultom, Andri Fransiskus (Sophia Dharma: Jurnal Filsafat, Agama Hindu, dan Masyarakat, 2023)
Existential isolation has become a problem that makes anxiety. Existential isolation is an academic term for ramification in three fields of science namely phenomenology, humanistic psychology, and existentialism. All three fields are in the realm of philosophy. Existential isolation in phenomenology focuses on the individual's direct experience and personal understanding of reality as the main subject that is worthy of attention. This research employed the existential-phenomenological method by investigating the mode of human existence in the pandemic situation. A study of existential isolation is illustrated by two characters, Rieux and Paneleux, in Albert Camus' novel, La Peste. The results of this study are (1) the meaning of existential isolation was anxiety and fear of death; (2) the existential isolation of Camus was in Rieux and Paneloux while witnessing death and then experiencing solitude. Kierkegaard's existential isolation exists in childhood experiences as his father gives examples of unscrupulous life and the cancellation of an engagement with Regine Olsen; (3) the juxtaposition between Camus and Kierkegaard's thoughts for citizens of Indonesia can be found in the idea of subjectivity, the vitality of life, and communication. The recommendations of this research are anchored in the ethics of care in the pandemic era.